Increased susceptibility to complicated pneumonia among egyptian children with FokI (rs2228570), not TaqI (rs731236), vitamin D receptor gene polymorphism in association with vitamin D deficiency: a case-control study - Mahitab Morsy Hussein; Enas Maher Mohamed; Tarek Mostafa Kamal; Tharwat Ezzat Deraz (BMC, 2023)
Abstract Background Determining a genetic contribution to the development of complicated community-acquired pneumonia in children may help understand underlying pathogenesis. We aimed to investigate the association between two vitamin D receptor (VDR) gene polymorphisms, FokI and TaqI, and susceptibility to complicated pneumonia in Egyptian children compared to uncomplicated pneumonia. Associations with 25 hydroxy-vitamin D serum level were studied. Methods This was a case-control study that included 320 participants divided into 2 groups: patients and controls. The patients' group included 100 children hospitalized with complicated pneumonia and 100 with uncomplicated pneumonia. 120 age and sex-matched apparently healthy children served as controls. The VDR FokI and TaqI polymorphisms were genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. 25 hydroxy-vitamin D level was estimated in serum using ELISA. Results Regarding FokI, homozygous CC genotype was more common in complicated (52%) than uncomplicated pneumonia (28%) and controls (10%) (OR = 65; 95%CI (5.13-822.63), p < 0.001) and (OR = 4.3; 95%CI (0.7-27.16), p = 0.003), respectively. Children carrying C allele possessed 3 higher odds for complicated than uncomplicated pneumonia (OR = 3.08; 95%CI (1.33-7.14), p < 0.001). Heterozygous CT genotype increased susceptibility to complicated pneumonia (OR = 13.7; 95%CI (4.6-40.1), p < 0.001), not uncomplicated pneumonia (OR = 1.56; 95%CI (0.86-2.85), p = 0.145). Among complicated pneumonia, vitamin D level was lower in CC (6.92 ± 2.6ng/ml) than CT (9.55 ± 3.2 ng/ml) and TT genotype carriers (13.13 ± 3.6ng/ml) (p < 0.001). There was no significant difference between patients and controls as regards TaqI genotypes and alleles. Conclusion In association with vitamin D deficiency, VDR gene FokI polymorphism, not TaqI, is a genetic risk factor for complicated pneumonia in Egyptian children.